A case study : Reading poetry among form one students in a secondary school in Sarawak / Atung Asaul - Asaul, Atung (2011)
This study aims at identifying how Form One students feel about reading poetry; whether they like to read poetry and also if they find it easy or difficult to read poetry. It also identifies the factors of the difficulties as well as the strategies employed by these students. Data for this study were collected through the administration of group interviews over a period of two weeks by using both questionnaire interview and open-ended interview questions. The interview sessions are audio- taped, transcribed, analyzed and reported in percentages and described qualitatively. There were one hundred and thirty five Form One students in one of the school in Sarawak involved in this study. The findings indicate that a majority of the students dislike reading poetry. Besides that, a majority of them also have difficulties in understanding some archaic, unfamiliar words, to interpret the message of the poems as well as the meaning of the poems as they claimed that the poems were linguistically difficult. Most students prefer consulting the dictionary, teacher, family members or friends when they faced difficulties in understanding the poems in order to address the difficulties faced in reading poetry.